A floresta nacional de Tefé e a universidade: lugares de construção de intelectualidades - Amaro , Cristiany Torres de Carvalho (2018)
This work presents results of our research whose reflection sought to understand some ways of thinking about the practices proposed and developed in the Young Protagonists Project through articulation of the various social subjects (public servants, community youth, students and university teachers) insofar as it conceives the Project as an educational space that makes it possible to unveil possible colonizing practices in a joint effort to demystify the colonialist ideology that conceals and eludes through democratic discourses a context of immobility and resistance designed by the colonial situation. Our research is based on the perspective of the Postcolonial Studies, putting in dialogue such authors as Aimé Césaire (1978), Albert Memmi (2007), Frantz Fanon (1968), Paulo Freire (1987), Casanova (2007), Silvia R. Cusicanqui (2010), among others, which helped us to construct analysis tools in order to perceive some possibilities of mobility in a scenario of oppression, articulating the possibility of the Young Protagonists Project to contribute to a continuous and necessary action- reflection on intellectual making and possible construction of knowledge which appreciates the scientific and traditional knowledge of the Middle Solimões populations, a "Ribeirinha Science" in the attempt to surpass colonialist practices of the knowledge, of the being, of the doing.